2011
DOI: 10.1111/j.1444-0938.2010.00552.x
|View full text |Cite
|
Sign up to set email alerts
|

Community‐based diabetic retinopathy screening in Hong Kong: ocular findings

Abstract: Background: Diabetic retinopathy is one of the most common causes of blindness. Timely retinal evaluation is known to prevent or minimise visual loss. This study compared the prevalence of ocular disorders in patients who have and have not undergone a retinal examination since diagnosis of their type 2 diabetes mellitus (T2DM). Such data might be useful for planning purposes by health care authorities and agencies in Hong Kong. Methods: Patients with T2DM aged 30 years or over presented for standardised interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In one study on a selected population with DM in HK, the prevalence of DR was 28.4% 18. In another community-based screening programme in a selected population from an integrative community health centre, the prevalence of DR was 30.7% 19. It is difficult to compare these estimates with our study due to the selection of populations and different definitions of DR.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In one study on a selected population with DM in HK, the prevalence of DR was 28.4% 18. In another community-based screening programme in a selected population from an integrative community health centre, the prevalence of DR was 30.7% 19. It is difficult to compare these estimates with our study due to the selection of populations and different definitions of DR.…”
Section: Discussionmentioning
confidence: 58%
“…Nearly one in three had some level of DR which confers a higher risk of progression to STDR and nearly one in 10 had STDR already which requires referral to a specialist ophthalmology clinic for follow-up and treatment. Very few studies have previously identified the prevalence of DR in HK18 19 and none have included, like our study, all those who attend public primary care clinics. In one study on a selected population with DM in HK, the prevalence of DR was 28.4% 18.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the mean patient age of 44.2 years in our study is also younger than that of 60 years in previous studies. 16,17 This might explain why our patients have a lower prevalence of DR than previously published data. 7 Our relatively younger DM population also accounts for the lower percentage (2.5%) of ungradable photographs owing to the presence of cataracts.…”
Section: Discussionmentioning
confidence: 45%
“…We used real-world data from a 7-month public screening service to reflect the reality of implementing this diagnostic AI tool in daily clinical practice. The high proportion (more than half) of newly diagnosed DM patients might be related to our hospital setting, 16 as these DM patients might be at the stage of oral hypoglycemic agents and insulin titration and have not yet stepped down to family medicine or general outpatient clinics for regular medication refills. However, this phenomenon could also result from better patient compliance with DR screening soon after diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…[4] DR screening aims to identify an unnoticed complication of diabetes, as most patients with diabetes do not realize they have DR until their vision is already affected. [5] One Hong Kong study showed that patients with diabetes who do not attend screening are up to 4 times higher risk for developing sight-threatening DR. [6] Further, DR screening has the potential to detect retinal and microvascular conditions other than DR contributing to improved overall eye health. [7] While DR screening is critical for disease management, low-resource settings, such as Rwanda often lack the infrastructure and trained personnel to implement DR screening programs effectively.…”
Section: Introductionmentioning
confidence: 99%